2009
DOI: 10.1080/00029890.2009.11920975
|View full text |Cite
|
Sign up to set email alerts
|

Ramanujan's Series for 1/π: A Survey

Abstract: When we pause to reflect on Ramanujan's life, we see that there were certain events that seemingly were necessary in order that Ramanujan and his mathematics be brought to posterity. One of these was V. Ramaswamy Aiyer's founding of the Indian Mathematical Society on 4 April 1907, for had he not launched the Indian Mathematical Society, then the next necessary episode, namely, Ramanujan's meeting with Ramaswamy Aiyer at his office in Tirtukkoilur in 1910, would also have not taken place. Ramanujan had carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 46 publications
(20 reference statements)
1
48
0
3
Order By: Relevance
“…An excellent survey on Ramanujan-type series is [2] and a beautiful survey on recent advances is in [10]. There are many examples of convergent Ramanujan-type and Ramanujan-Sato-type series in the literature, the most spectacular are of simple and very fast series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent survey on Ramanujan-type series is [2] and a beautiful survey on recent advances is in [10]. There are many examples of convergent Ramanujan-type and Ramanujan-Sato-type series in the literature, the most spectacular are of simple and very fast series.…”
Section: Discussionmentioning
confidence: 99%
“…They are of the following form During a long time these Ramanujan's series for 1/π were almost ignored but since 1987 the interest of mathematicians in them was great. The 17 formulas as well as many other series of the same type are already proved rigorously [2]. Naturally, they are called Ramanujan-type series.…”
Section: Ramanujan and Ramanujan-sato Seriesmentioning
confidence: 98%
“…(см., например, [111]) могут быть получены единообразно благодаря доступно-му модулярному и гипергеометрическому аппаратам [30], [16], [181]. Подобная формула…”
Section: в в зудилинunclassified
“…В настоящее время уже практически нет ничего загадочного в классических формулах Рамануджана для представления 1/π, примеры которых -формулы (4)-(6) и их многочис-ленные обобщения. По этому вопросу мы рекомендуем читателю ознакомиться с монографией [30] и недавно опубликованными обзорами [16], [181]. В от-ношении данных формул примечательным является не только явное присут-ствие гипергеометрического ряда в левой части, но также наличие чисто ги-пергеометрического аппарата [51], [65], [67], позволяющего доказывать неко-торые из таких представлений.…”
Section: формулы рамануджанова типа для 1/πunclassified
“…These authors and several other authors in the past two decades have found many new series for 1/π as well as for 1/π 2 . We refer to [4] for a recent survey on Ramanujan's series for 1/π.…”
Section: Introductionmentioning
confidence: 99%